2016
DOI: 10.1161/atvbaha.116.307739
|View full text |Cite
|
Sign up to set email alerts
|

Central Role of P2Y 6 UDP Receptor in Arteriolar Myogenic Tone

Abstract: Objective Myogenic tone (MT) of resistance arteries ensures autoregulation of blood flow in organs and relies on the intrinsic property of smooth muscle to contract in response to stretch. Nucleotides released by mechanical strain on cells are responsible for pleiotropic vascular effects, including vasoconstriction. Here, we evaluated the contribution of extracellular nucleotides to MT. Approach and Results We measured MT and the associated pathway in mouse mesenteric resistance arteries using arteriography … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
49
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 71 publications
(55 citation statements)
references
References 55 publications
6
49
0
Order By: Relevance
“…These findings are in accordance with experiments performed in vitro and in gene modified animals demonstrating a coupling between Panx1 channels and α1-adrenoceptors 46 and suggest a functional role of Panx1 channels in setting resting tone via α1-adrenoceptors in humans. The increase in heart rate probably represents a baroreflex-mediated effect to maintain MAP at a reduced total peripheral resistance, but direct cardiac effects cannot be excluded.…”
Section: Discussionsupporting
confidence: 91%
“…These findings are in accordance with experiments performed in vitro and in gene modified animals demonstrating a coupling between Panx1 channels and α1-adrenoceptors 46 and suggest a functional role of Panx1 channels in setting resting tone via α1-adrenoceptors in humans. The increase in heart rate probably represents a baroreflex-mediated effect to maintain MAP at a reduced total peripheral resistance, but direct cardiac effects cannot be excluded.…”
Section: Discussionsupporting
confidence: 91%
“…However, deletion of SMC Panx1 did not alter the development of myogenic tone in cerebral arteries ( Figure 5, D and E). These data, coupled with the data above, suggest that EC Panx1 may regulate severity of cerebral ischemia/reperfusion injury Previous work has demonstrated that mesenteric arteries also utilize purinergic signaling to regulate myogenic tone, and Panx1 is expressed within the ECs of mesenteric arteries (11,26,27). In concordance with those experiments, we found that carbenoxolone treatment, which inhibits both Panx1 and Cx43 channels, significantly reduced myogenic tone development in third-order mesenteric arteries ( Figure 6, A-C), whereas spironolactone treatment, which does not inhibit Cx43 channels (25), did not impact mesenteric myogenic tone development ( Figure 6, D-F).…”
Section: Resultsmentioning
confidence: 57%
“…As a third aspect, Izzard and others discuss the issue that myogenic tone can protect vessels from vascular hypertrophy by lowering wall stress, which has been proposed to be the stimulus for hypertrophy (Izzard et al 2005). Recent studies have provided evidence that the G protein-coupled receptor (GPCR) mediated signaling is involved (Schnitzler et al 2008;Schleifenbaum et al 2014;Hui et al 2015;Storch et al 2015;Kauffenstein et al 2016) but mechano-activated ion channels (Welsh et al 2002;Drummond et al 2004;Earley et al 2004;Bulley et al 2012) and interactions between extracellular matrix proteins and membranespanning integrins (Martinez-Lemus et al 2003Jackson et al 2010;Colinas et al 2015) are also thought to contribute to the upstream sensing of pressure in the myogenic response. More detailed knowledge of the signaling pathways in the myogenic response is needed for a more complete understanding of the pathogenesis of hypertension and conditions that entail important risk factors for hypertension, such as: aging, abdominal obesity, diabetes, chronic mental stress, excess salt intake, high cholesterol, lack of physical exercise, or sleep apnea.…”
Section: Introductionmentioning
confidence: 99%